Composição e diversidade da ictiofauna do Ribeirão Poço Grande, afluente do Rio Juquiá, Bacia do Rio Ribeira de Iguape, estado de São Paulo - Costa, Rafael Maribelto da (2018)
The Atlantic Forest, considered the second largest tropical rainforest in the Americas, is one of the richest ecosystems in plant and animal species in the entire planet. The water catchment area of the Ribeira de Iguape river, located in the south of the State of São Paulo, is located in the region where there are the largest extensions of preserved Atlantic Forest on the Brazilian coast. Of the species of fish registered to Brazil, part can be found in the streams of the Atlantic Forest, which due to the high degree of endemism and to the natural characteristics of these environments, are important in the context of freshwater fish. Among the main threats to fish in streams of the Atlantic Forest are the destruction of riparian forests, bushes and the introduction of exotic species. This study was carried out in the Juquiá river and its tributary, Poço Grande, in the Ribeira de Iguape river basin, in the municipality of Juquiá, São Paulo state, with the main objective of inventorying the ichthyofauna of these two environments. First, the analysis of lots of fish collected both in the Juquiá river and in the Poço Grande stream, deposited in the collections of the Laboratório de Ictiologia Sistemática do Departamento de Ecologia e Biologia Evolutiva da UFSCar (LISDEBE - UFSCar) and of the Museu de Zoologia da Universidade de São Paulo, resulted in an initial list of species. Additions to this list were made from a collection held in June 2018 using trawls, gillnets, containment net and electric fishing. The collection was performed at 5 sampling stretches with approximately 100 meters each for a period of 2 hours. Collection and sampling data resulted in a list of species for the river Juquiá and Ribeirão Poço Grande. Also it is presented a historical portrait of the collections made in the Poço Grande creek for 120 years (from 1898 to 2018). These data and the list of species recently collected allowed the evaluation of fish diversity in this area of Ribeira de Iguape basin through the Shannon-Weaver Index and the rarefaction method. The orders Characiformes and Siluriformes were the most representative, as well as the families Characidae and Loricariidae. Although the ichthyofauna of Poço Grande may be considered well known, the study area still needs a greater effort of collections, chiefly in the river Juquiá and other tributaries, which have not their ichthyofauna adequately known.